Koreografi Tari Galuik Salendang Sanggar Tuah Sakato di Kota Padang - Siti Aisah; Susmiarti Susmiarti (SENDRATASIK UNP, 2023)
This study aims to reveal and describe the Choreography of the Galuik Salendang Sanggar Tuah Sakato Dance in the City of Padang. This type of research is qualitative research with descriptive methods of analysis. This research instrument is the researcher himself and is assisted by supporting instruments in the form of stationery, cameras and audio recording devices. Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The steps of analyzing data are data collection, data reduction, data presentation and drawing conclusions. The results showed that the creation of Galuik Salendang dance consisted of 2 aspects, namely the content aspect and the form aspect. The content aspect consists of ideas, atmospheres and functions. The idea of creating Galuik Salendang dance was inspired by the Sofyani Umbrella dance and the pre-existing Galuik Salendang dance. The atmosphere of this dance is a joyful and passionate atmosphere. The function of Galuik Salendang dance is as an entertainment dance. While the form aspect consists of movement, dancers, floor design, dramatic design, group composition, costumes, props and dance accompaniment